Mouse Genetic Background Affects Transfer of an Antibiotic Resistance Plasmid in the Gastrointestinal Tract - Logan C. Ott (American Society for Microbiology, 2020)
ABSTRACT Dissemination of antibiotic resistance (AR) genes, often on plasmids, leads to antibiotic-resistant bacterial infections, which is a major problem for animal and public health. Bacterial conjugation is the primary route of AR gene transfer in the mammalian gastrointestinal tract. Significant gaps in knowledge about which gastrointestinal communities and host factors promote plasmid transfer remain. Here, we used Salmonella enterica serovar Kentucky strain CVM29188 carrying plasmid pCVM29188_146 (harboring streptomycin and tetracycline resistance genes) to assess plasmid transfer to Escherichia coli under in vitro conditions and in various mouse strains with a conventional or defined microbiota. As an initial test, the transfer of pCVM29188_146 to the E. coli strains was confirmed in vitro. Colonization resistance and, therefore, a lack of plasmid transfer were found in wild-type mice harboring a conventional microbiota. Thus, mice harboring the altered Schaedler flora (ASF), or ASF mice, were used to probe for host factors in the context of a defined microbiota. To assess the influence of inflammation on plasmid transfer, we compared interleukin-10 gene-deficient 129S6/SvEv ASF mice (proinflammatory environment) to wild-type 129S6/SvEv ASF mice and found no difference in transconjugant yields. In contrast, the mouse strain influenced plasmid transfer, as C3H/HeN ASF mice had significantly lower levels of transconjugants than 129S6/SvEv ASF mice. Although gastrointestinal members were identical between the ASF mouse strains, a few differences from C3H/HeN ASF mice were detected, with C3H/HeN ASF mice having significantly lower abundances of ASF members 356 (Clostridium sp.), 492 (Eubacterium plexicaudatum), and 502 (Clostridium sp.) than 129S6/SvEv ASF mice. Overall, we demonstrate that microbiota complexity and mouse genetic background influence in vivo plasmid transfer. IMPORTANCE Antibiotic resistance is a threat to public health. Many clinically relevant antibiotic resistance genes are carried on plasmids that can be transferred to other bacterial members in the gastrointestinal tract. The current study used a murine model to study the transfer of a large antibiotic resistance plasmid from a foodborne Salmonella strain to a gut commensal E. coli strain in the gastrointestinal tract. We found that different mouse genetic backgrounds and a different diversity of microbial communities influenced the level of Escherichia coli that acquired the plasmid in the gastrointestinal tract. This study suggests that the complexity of the microbial community and host genetics influence plasmid transfer from donor to recipient bacteria.